1996
DOI: 10.1007/bf02246177
|View full text |Cite
|
Sign up to set email alerts
|

Differential responsiveness of inbred strains of rats to antidepressants in the forced swimming test: are Wistar Kyoto rats an animal model of subsensitivity to antidepressants?

Abstract: In three experiments we have studied the effects of acute administration of various doses (5, 10, 15 and 25 mg/kg) of desipramine (DMI) and two doses (0.5 and 2 mg/kg) of 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT), a selective 5HT1A receptor agonist, on behaviour of five inbred strains of rats in the holeboard and the forced swimming test (FST). The strains were Brown-Norway (BN), Fischer 344 (FIS), Lewis (LEW), Spontaneously Hypertensive Rats (SHR) and Wistar-Kyoto (WKY). In drug-free conditions, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 38 publications
1
62
0
Order By: Relevance
“…18,[23][24][25][26][27]31,33 Their behavior in the FST and several other behavioral tests provide strong evidence that WKY rats are in a depressive-like state. While both WKY and F344 females exhibit high levels of immobility, WKY females did exhibit decreased climbing in the FST relative to F344 females.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…18,[23][24][25][26][27]31,33 Their behavior in the FST and several other behavioral tests provide strong evidence that WKY rats are in a depressive-like state. While both WKY and F344 females exhibit high levels of immobility, WKY females did exhibit decreased climbing in the FST relative to F344 females.…”
Section: Discussionmentioning
confidence: 97%
“…5 The Wistar Kyoto (WKY) rat exhibits depressivelike behavior in a number of behavioral tests. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Among the behavioral tests that indicate a depressivelike state in the WKY, we chose to work with the forced swim test (FST), a measure frequently used to test for antidepressant drugs. This test is used in animal models to test for 'behavioral despair' [35][36][37][38] and/or 'passive coping behavior'.…”
Section: Introductionmentioning
confidence: 99%
“…However, these results disagree with those of Lahmame, Armario, and associates. These investigators reported that WKY rats were subsensitive in their response to the acute administration of desipramine or imipramine in the FST, although they did respond to chronic treatment with imipramine (15 mg/kg, once daily for 14 days) (Lahmame and Armario 1996;Lahmame et al 1997). A number of procedural differences might contribute to the discrepant results between Lahmame and those of Paré and ourselves, although both laboratories use FST scoring procedures that measure active behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…It this context, it is noteworthy that on acute, but not repeated administration, WKY rats are resistant to the anti-immobility effect of the nonselective 5-HT reuptake inhibitor, imipramine, in the forced swim test (Lahmame et al 1997). In the latter case, serotonergic, but also noradrenergic systems may be involved as WKY rats (and SHRs) are resistant to the antiimmobility effect of the noradrenaline reuptake inhibitor desipramine (Lahmame and Armario 1996). In the present study, the possibility that the resistance of WKY rats to citalopram-elicited hypolocomotion involves the failure of the drug to reach serotonergic neurones and/ or to inhibit 5-HT reuptake was then examined.…”
Section: Strain-related Differences In the Behavioural Effects Of Citmentioning
confidence: 99%